O planejamento urbano-regional em Minas Gerais: vanguarda, experiências e ecos - Gabriel do Carmo Lacerda (2025)
This thesis analyzes the theoretical-methodological and practical existence of urban-regional planning in Minas Gerais. Its emergence and consolidation, especially in the 1970s, are the result of a process of acclimation and maturation initiated in the 1940s and intensified within the context of the civil-military dictatorship, which fostered synergies generating innovations, contradictions, continuities, and limitations. In Part I, the study highlights the origins of this development, evidenced by the initial contribution of FACE and later by UFMG’s CEDEPLAR. During this period, a “missing link” is emphasized: the influence of American Economic Geography, which sparked a concern with the spatial analysis of economic and social phenomena in the 1940s and 1950s, encouraging an innovative approach that incorporated space and Geography as explanatory elements for the differences between countries and regions while reinforcing the importance of state action. Subsequently, French contributions mark a turning point, when economic concepts allied with the emergence of Development Economics consolidated the emphasis on Regional Economics, culminating in the establishment of CEDEPLAR. In the 1960s and 1970s, innovative theoretical-methodological proposals emerged in the fields of Regional and Urban Economics and urban-regional planning, further complemented by Dutch influence. In Part II, the work systematizes material on spatial planning in Minas Gerais, focusing on experiences during the peak of the civil-military dictatorship, where the actions of the Fundação João Pinheiro (FJP) reveal the maturation and increasing complexity of spatial analyses, emphasizing multiple scales and reaffirming the integration between urban and regional analyses. Finally, Part III discusses the echoes of this experience, highlighting the continuities, limitations, contradictions, and criticisms in Minas Gerais’ urban-regional planning; the proposed periodization shows that although methodological advances occurred, spatial structuring transformations also reflect the spatial development of Brazilian capitalism, while the analysis in Revista Fundação JP illustrates how FJP technicians developed innovative and critical approaches to the regime, emphasizing the challenges imposed by state action and intra-bureaucratic constraints during the period.